Retroperitoneal Malignant Fibrous Histiocytoma Can Mimic a Hydatid Cyst - Gurcan Erbay; Serife Ulusan; Zafer Koc; Emine Tuba Canpolat; Kenan Calıskan (Case Reports in Radiology)
Malignant fibrous histiocytoma is the second most common soft-tissue sarcoma in adults. After the extremities, the retroperitoneal space is the second most common site of this tumor. A 50-year-old man presented with a right retroperitoneal, thick-walled, cystic multilocular mass measuring 10 × 10 cm that was thought to be a type CE 5 hydatid cyst preoperatively. However, the postoperative histopathology did not agree with the radiological findings and instead showed a malignant fibrous histiocytoma. The computed tomography and ultrasound/Doppler ultrasound findings of this retroperitoneal mass mimicked a type CE 5 hydatid cyst. We present this case because the surgical management of these two lesions differs and misdiagnosis can be problematic.